Allergic rhinoconjunctivitis - Miraglia Del Giudice, Michele; Allegorico, Annalisa; Marseglia, Gian Luigi; Martelli, Alberto; Calvani, Mauro; Cardinale, Fabio; Duse, Marzia; Chiappini, Elena; Manti, Sara; Cravidi, Claudio; Tosca, Maria Angela; Caffarelli, Carlo (Acta Biomedica Atenei Parmensis, 2020)
Allergic rhinitis (AR) is induced by an IgE-mediated immune reaction after allergen exposure. The typical symptoms are itching, nasal discharge, sneezing and nasal obstruction. The diagnosis is based on the concordance between allergic symptoms and diagnostic tests. The skin prick test (SPT) is recommended as the “gold standard” method. First generation H1-antihistamines are widely used for treatment of AR. Intranasal glucocorticosteroids are well tolerated and can be used also in paediatric age. Allergic rhinitis cannot be considered as an isolated pathology. Other atopic diseases (allergic conjunctivitis, atopic eczema, asthma) are commonly associated.